Bioentrepreneurship Ability Profile of Students in Microbiology Learning - Nurwahyunani, Atip; Wiyanto, Wiyanto; Rusilowati, Ani; Susilaningsih, Endang (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2021)
Graduates from undergraduate education contributed 6.31% to the unemployment rate. The Higher Education is expected to develop curriculum and learning not only scientifically oriented, but also facilitate life skills for its graduates. This study aims to analyze the profile of students about microbiology learning based on bioentrepreneurship. The research method is descriptive exploratory. The research subjects were 60 students who had taken microbiology courses in the Biology Education Study Program at FPMIPATI, Universitas PGRI Semarang, which consisted of semesters 7, 9, and 11. The instrument was a closed questionnaire with a choice of answers using the Guttman scale. A questionnaire on student perceptions of microbiology learning based on bioentrepreneurship was developed referring to perceptual indicators, namely knowledge and interest in entrepreneurship, knowledge of microbiology, relevance of microbiology concepts, bioentrepreneurship. Indicators developed in 25 questions and validated by experts and valid. The results showed that overall, the average score was 2.17. From each element, the highest average score is the Innovation element (3,4) and the lowest score from organizational creation and growth (1). Based on the data, the bioentrpreneurship profile is still low. Therefore, it is necessary to recommend the development of a learning program oriented towards bioentreprenurship in microbiology lectures.